1994
DOI: 10.1111/j.1476-5381.1994.tb17066.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for P2‐purinoceptor‐mediated inhibition of noradrenaline release in rat brain cortex

Abstract: 1 Some postganglionic sympathetic axons possess P2Y-like P2-purinoceptors which, when activated, decrease the release of noradrenaline. We examined the question of whether such receptors also occur at the noradrenergic axons in the rat brain cortex. Slices of the brain cortex were preincubated with pH]-noradrenaline, then superfused with medium containing desipramine (1 gM) and stimulated electrically, in most experiments by trains of 4 pulses/100 Hz.2 The selective adenosine Al-receptor agonist, N6-cyclopenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 56 publications
6
60
1
Order By: Relevance
“…However, a similar result was reported by von Kugelgen et al (1994), who found that high concentrations of APNEA had no effect on adenosine Al receptors in the rat brain cortex.…”
Section: Discussionsupporting
confidence: 65%
“…However, a similar result was reported by von Kugelgen et al (1994), who found that high concentrations of APNEA had no effect on adenosine Al receptors in the rat brain cortex.…”
Section: Discussionsupporting
confidence: 65%
“…The superficial slice was discarded, and round slices of 400 m (Microtome Leica VT1000S, Nussloch, Germany) were incubated for 45 min in a warmed (37°C) and gassed (95% O 2 -5% CO 2 ) Krebs solution with the following composition (mM): 118 NaCl, 4.7 KCl, 2. (von Kügelgen et al 1994). Briefly, occipital-parietal cortical brain slices were incubated in 2 ml of Krebs solution containing 0.1 M [ 3 H]NE (specific activity of 1.65 TBq/mmol) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The purinergic receptors, in particular the P2Y receptors, which include eight subtypes, P2Y 1,2,4,6,11,12,13,14 (Abbracchio et al 2006), have also been shown to play a relevant role in the regulation of synaptic transmission in several brain regions (Gonçalves and Queiroz 2008;Sperlágh et al 2007), participating in the modulation of neuronal transmitter release. Cortical norepinephrine release evoked by electrical stimulation was shown to be modulated by P2Y receptors (von Kügelgen et al 1994), but the subtypes of P2Y receptors have not been identified.…”
mentioning
confidence: 99%
“…Thus, it has been reported that P2Y-like receptor activation inhibits noradrenaline release from rat cerebral cortical [126] and hippocampal slices [145], and there is a hint that P2X receptor activation may facilitate noradrenaline release in the rabbit cerebral cortex [130].…”
Section: Noradrenalinementioning
confidence: 99%
“…epj, excitatory junction potential; epp, endplate potential; epsc, excitatory postsynaptic current; mepp, mini epp; NMJ, neuromuscular junction; sepp, spontaneous epp; NT, neurotransmitter. studies showed that ATP [124] and ATP analogues inhibit the evoked release of noradrenaline, but it was not clear if this action involves the activation of either P2Y-like receptors [125][126][127][128][129], adenosine A 1 receptors [130] or a proposed mixed ATP/adenosine receptor, named P3 receptor [55][56][57]131]. Other studies (Table 1) showed that activation of P2-like receptors facilitates evoked release of noradrenaline, and this action was proposed to involve either 'atypical' P2Y-like receptors [132,133] or P2X receptors [121].…”
Section: Noradrenalinementioning
confidence: 99%